Character Values in Children Songs Lyrics by Sumaryanto as an Effort to Develop Children's Personality - Wulansari, Reni; Wadiyo, Wadiyo; Triyanto, Triyanto (Universitas Negeri Semarang, 2020)
Children song by Sumaryanto is a learning medium that was created with the character values contained. The purpose of this study is to analyze and describe the values contained in children songs by Sumaryanto that can shape a child's personality. The method used is qualitative with a psychological approach and arts education. The data collection techniques was conducted through observation, interviews, and document study. The data validity technique used was the source triangulation technique. The analysis process was started from data collection, data reduction and clarification, drawing conclusions and interpretation. The results showed that children songs by Sumaryanto have character values that can help children's development. The values including the values of caring for the environment, the value of curiosity, the value of respect for parents, and the value of honesty. These values appeared through the lyrics contained in every song by Sumaryanto which certainly had a good impact on children by implementing these good qualities.